THE APPLICATION OF SHARIAH (ISLAMIC LAW) IN SOME DIFFERENT COUNTRIES AND ITS IMPLICATIONS - Gulam, Hyder (Jurnal Syariah, 2017)
This paper will explore the meaning of Shariah and examines its application in specified countries around the world. The implications of the application on the development of Shariah will also be discussed by collating the writings of various scholars on the subject in the contemporary world. This paper will show that Shariah does not need formal legal recognition to be applied, as in the example of Australia where there is a Muslim-minority and there is no formal Islamic law. Other examples include the application of Shariah in Aceh and Singapore, which showcase a dynamic relationship between Islamic law and civil rulings. Shariah is supremely malleable and adaptable to many different situations and continues to evolve. By and large, the development of Shariah in non-Muslim states has shown that Muslims are readily able to comply with the laws of the land, while accommodating generally the various demands of religious legal obligations.